MOTIVATIONAL BONUSES TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN DI INDONESIA - Nurul Hasanah M Zach; Mochammad Ilyas Junjunan; Binti Shofiatul Jannah; Ajeng Tita Nawangsari; Selvia Eka Aristantia (Accounting Journal of Ibrahimy (AJI), 2024)
This study aims to examine the influence of leverage, motivational bonuses, and company size on earnings management. The research focuses on banking companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. The sampling technique employed is purposive sampling, resulting in data from 16 companies with 80 observations over a 5-year period. The data analysis method used in this research is multiple linear regression with EViews 10. The results of the data analysis indicate that leverage, and company size do not have a significant impact on earnings management. However, motivational bonuses show a negative influence on earnings management. Based on these findings, companies continue to implement strict supervision of management to prevent earnings management actions. Providing bonuses has proven to be effective in minimizing earnings management, thereby preserving the credibility of financial reports presented to the public. Recommendations for future researchers include adding other variables, such as profitability and institutional ownership, as additional factors. Additionally, extending the observation period or using subjects other than banking companies could be explored in further studies.